Armadillo Ray - Beifuss, John, 1959-; Turley, Peggy; Antreasyan, Agustín (San Francisco : Chronicle Books, 1995)
Curious about the true nature of the moon, Armadillo Ray asks different animals for their opinion.
K-3
Text in Spanish.
Translation of: Armadillo Ray.
K-3
Elem. School Library Collection
School Library Journal
Keywords: Armadillos -- Fiction; Desert animals -- Fiction; Spanish language materials; Moon -- Fiction; Armadillos -- Fiction; Desert animals -- Fiction; Spanish language; Moon -- Fiction